2022
DOI: 10.3233/nre-210315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wheelchair type on Wheelchair Propulsion Test performance in community-dwelling, adult wheelchair users1

Abstract: BACKGROUND: The clinimetric properties of the Wheelchair Propulsion Test (WPT) have not been developed thoroughly. OBJECTIVE: To determine inter-rater reliability and reference values for the Wheelchair Propulsion Test (WPT) for active wheelchair users and to compare WPT performance between various types of manual wheelchairs at different paces. METHODS: This was a cross-sectional, descriptive study. Participants propelled a manual wheelchair 10 m while time and the number of pushes were recorded. Trials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Damen et al (2020) used the 6MPT to evaluate 53 young individuals between the ages of 5 and 19 to verify its accuracy against standard in-clinic measurements for physical activity and concluded that "the 6MPT is a reliable, functional performance test on a vigorous level of exercise." One thing to consider when utilizing a test like the 6MPT is that, according to a 2022 study by Andrews et al (2022) MWU "who utilize their personal wheelchair demonstrate faster wheelchair propulsion speeds complimented by greater push frequencies" compared to unfamiliar wheelchairs.…”
Section: Clinical Measurementmentioning
confidence: 99%
“…Damen et al (2020) used the 6MPT to evaluate 53 young individuals between the ages of 5 and 19 to verify its accuracy against standard in-clinic measurements for physical activity and concluded that "the 6MPT is a reliable, functional performance test on a vigorous level of exercise." One thing to consider when utilizing a test like the 6MPT is that, according to a 2022 study by Andrews et al (2022) MWU "who utilize their personal wheelchair demonstrate faster wheelchair propulsion speeds complimented by greater push frequencies" compared to unfamiliar wheelchairs.…”
Section: Clinical Measurementmentioning
confidence: 99%